A randomized study of surgical site infiltration with bupivacaine or ketamine for pain relief in children following cleft palate repair. Issue 5 (28th February 2013) - Jha, Ajay Kumar; Bhardwaj, Neerja; Yaddanapudi, Sandhya; Sharma, Ramesh Kumar; Mahajan, Jai Kumar; Bosenberg, Adrian
Summary Background Wound infiltration with ketamine reduces postoperative pain after tonsillectomy by NMDA receptor blockade and local anesthetic effect. Objectives To evaluate the postoperative analgesia after surgical site infiltration with bupivacaine or ketamine in children undergoing cleft palate surgery. Materials and methods After institutional ethics committee approval and parental consent, 50 ASA‐1 children of age 1–6 years undergoing palatoplasty were included in this prospective randomized double‐blind study. A standardized technique of general anesthesia was used. The surgical site was infiltrated with either 2 mg·kg−1 of bupivacaine (Group B) or 0.5 mg·kg−1 of ketamine (Group K). Pain (Children Hospital Eastern Ontario Pain Score), sedation, dysphagia, nausea, vomiting, and sleep pattern were assessed postoperatively up to 24 h. Results CHEOPS scores were similar in both the groups up to 12 h but were lower with ketamine compared with bupivacaine at 24 h postoperatively (P = 0.01). Fewer children required rescue analgesics in Group K (28%) than in Group B (64%; P < 0.01). The time to first rescue analgesic and the amount of analgesics used in 24 h were similar in the two groups. Fewer children suffered from dysphagia in Group K (52%) than in Group B (88%; P < 0.01). More children in Group B had disturbed sleep than in Group K at 6 (88% vs 56%; P = 0.012) and 12 h (60% vs 24%; P = 0.01) postoperatively. None of the children had deep sedation, desaturation or respiratory depression. Conclusion Surgical site infiltration with either bupivacaine or ketamine provides adequate analgesia and is devoid of major side effects. Ketamine is superior to bupivacaine in terms of requirement of rescue analgesic, peaceful sleep pattern and early resumption of feeding.